Investigating determinants of effective game-based learning implementation in primary education - Dao Thi Thai; Chi Thi Diep Nguyen; Tuan Anh Phan; Dung Tien Nguyen; Giang Thi Chau Nguyen (Institute of Advanced Engineering and Science, 2026)
The purpose of this study is to identify the factors influencing the organization of game-based learning (GBL) activities in primary schools and to validate the reliability, validity of these factors. The research sample consisted of 621 primary school teachers, randomly divided into two groups: 311 samples were used for exploratory factor analysis (EFA), and 310 samples for confirmatory factor analysis (CFA). The EFA results uncovered seven latent factors, accumulating for over 68.995% of the data variance. The CFA validated the seven-factor model, with model fit indices passing acceptable standards, implying high reliability and validity of the measurement structure. The primary factors influencing the organization of GBL activities in primary schools include confirmation, teaching environment, students, belief, motivation, perception, and competence. The findings affirm that this seven-factor model accurately reflects critical dimensions of organizing GBL activities in our current context. Thus, these results provide a scientific foundation for teachers, educational administrators, and researchers to enhance and promote GBL activities in primary education effectively.